(untitled) (International Journal of Food and Nutritional Sciences, 2022)
It is a natural desire of humans to look stunning, young, and lovely. Compared to other parts of the skin, the skin surrounding the eyes is comparatively thin and has less fat. For this reason, puffiness, bags, pigmentation, and dark circles under the eyes are the first signs of aging, stress, illness, environmental pollution, melanin deposition, lifestyle, and genetics.